Call upon the water - Tillyard, S. K (Atria Books, 2019)
In 1649, Jan Brunt arrives in Great Britain from the Netherlands to work on draining and developing an expanse of marshy wetlands known as the Great Level. It is here in this wild country that he meets Eliza, a local woman whose love overturns his ordered vision. Determined to help her strive beyond her situation, Jan is heedless of her devotion to her home and way of life. When she uses the education Jan has given her to sabotage his work, Eliza is brutally punished, and Jan flees to the New World. In the American colonies, profiteers on Manatus Eyland are hungry for viable land to develop, and Jan's skills as an engineer are highly prized. His prosperous new life is rattled, however, on a spring morning when a boy delivers a note that prompts him to remember the Great Level and confront all that was lost there. Eliza has made it to the New World and is once again using the education Jan gave her to bend the landscape - this time to find her own place of freedom.